2014
DOI: 10.2534/jjasnaoe.19.79
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Primary Efficiency of a Wave Energy Converter "Backward Bent Duct Buoy" in regular wave conditions

Abstract: SummaryA primary conversion efficiency of a floating OWC-type wave energy converter "Backward Bent Duct Buoy (BBDB)" in regular waves is investigated in 2D and 3D wave tank tests. Firstly, the amplitude and phase difference between the internal wave height and motions are investigated. In a 3D tank test, surge, heave and pitch become in-phase at efficiency become maximum. The phase of internal wave height is close to motion. Secondary, the efficiency of duct-extended buoy is investigated in 2D test. Efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…(12), (14), or (15), and this will become evident when we look at the effect of the piston lengths later in the research. However, due to the interaction between the float body and the imaginary pistons, in the dynamic system, the mass and added mass must be considered together, as shown in Table II.…”
Section: Comments On the Piston Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…(12), (14), or (15), and this will become evident when we look at the effect of the piston lengths later in the research. However, due to the interaction between the float body and the imaginary pistons, in the dynamic system, the mass and added mass must be considered together, as shown in Table II.…”
Section: Comments On the Piston Representationmentioning
confidence: 99%
“…Toyota et al 14 have shown that both the size of the air chamber and the length of the horizontal duct length of a Backward Bent Duct Buoy (BBDB) device have significant effects on the primary power conversion of the OWC wave energy converters. Imai et al 15 have studied the influence of the horizontal duct length to the wave energy capture capacity in a BBDB device and shown that a longer horizontal duct has increased the maximum IWS response to a longer resonance period. As a result of this, a longer horizontal duct may be desirable for tuning the BBDB to the wave states of longer wave periods.…”
mentioning
confidence: 99%
“…Relevant wave energy conversion efficiencies for a number of OWC devices evaluated in wave tanks/flumes have been included in Table 2 , showing significant variations from one another. In this regard, 55 claims that a generic OWC has a relatively poor wave energy conversion efficiency of 7.5%, while in studies 56 the efficiency was found to be 35%. Wells turbine is limited to avoid stalling behaviour.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…1B shows the hydrodynamic counterpart (note only the wetted surface must be modeled for the potential flow BEM solver). The width of the device is 27 m. The majority of the device dimensions were selected based upon the conclusions of the following papers Imai et al (2011), Suzuki et al (2011), and Hong et al (2004. The ballast is assumed to be seawater and is added to the buoyancy chambers as shown in Fig.…”
Section: Bbdbmentioning
confidence: 99%